A aventura de uma estudante estagiária a caminho de se tornar Professora de Educação Física - Margarida dos Santos Correia (2021)
This document was written within the context of the school placement, included in the second year of the 2nd cycle in Physical Education Teaching in the Primary and Education, at the Faculty of Sports of the University of Porto. school placement,is the culmination of the preservice training and future teachers, since it is during this year that they are faced with the demands of the profession in a real context and seek to put into practice what they have learned during their training. The school placement (of the author) took place at a school located in Porto, as part of a practicum group consisting of three elements under the guidance of a Professor from the Cooperating School and of a Professor from the Faculty of Sports of the University of Porto. This pedagogical intervention occurred mostly with a 9th grade class, but with teaching experiences also taking place in a 6th grade class and in School Sports. Throughout this report, the experiences, actions and challenges that the author has faced throughout the year are reported, with a special focus on the first impressions of the meaning of "Being a Teacher" and on the pandemic that we were forced to face throughout the 2020/2021academic year. Hence, one of the greatest learning experiences retained by the autor is that the student must be valued as an asset in the teaching-learning process and the constant adaptation and (re)adaptation that a teacher must be able to perform in order to achieve the previously stipulated goal. The research study aimed to analyze students from three 9th grade classes of the Cooperating School and their experience in e-learning focusing on the importance of Physical Education for their well-being and to fight loneliness feelings. The results show the existence of a positive correlation between the impact of Physical Education classes and the well-being of students during the confinement period.